2014
DOI: 10.1007/s00383-014-3617-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of postoperative abscess occurrence and percutaneous drainage in children with perforated appendicitis

Abstract: The risk of a postoperative abscess can be predicted by specific clinical characteristics, surgical findings, and treatment-related factors. Percutaneous drainage was associated with longer hospital stays, but less readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 36 publications
4
20
1
2
Order By: Relevance
“…Similar to the results of previous studies [18,37], in our study, post-operative adverse events were associated with longer hospital stays.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to the results of previous studies [18,37], in our study, post-operative adverse events were associated with longer hospital stays.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicate that the presence of high-grade obstruction on pre-operative CT scan is an independent factor predicting postoperative adverse events. This result is supported by a previous study by Emil et al [18] including 284 children treated for perforated appendicitis over a 5-year period, which found that the presence of bowel obstruction at presentation was significantly associated with a sixfold increase in occurrence of post-operative abscess. However, these previous results showed some differences compared to those of the present study regarding age and severity of perforated appendicitis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Дискутабельними і не до кінця вирішеними за-лишаються питання адекватного хірургічного ліку-вання оментитів, недостатньо розроблені питання профілактики розвитку післяопераційних інфіль-тратів за участю сальника [4, 11, 12,13, 14, 15]. За-лишаються відкритими питання особливостей пато-морфологічних порушень при оментитах [1,6,16].…”
Section: вступunclassified
“…Оментити у дітей, за даними різних авторів, становлять 30 -35 % у загальному числі невід-кладних лапаротомій [1,4,5,6]. Будучи втягне-ним у запальний процес, великий сальник може ускладнити перебіг основного захворювання й стати причиною релапаротомії [2,7,8,9, 10 ].Дискутабельними і не до кінця вирішеними за-лишаються питання адекватного хірургічного ліку-вання оментитів, недостатньо розроблені питання профілактики розвитку післяопераційних інфіль-тратів за участю сальника [4, 11, 12,13, 14, 15]. За-лишаються відкритими питання особливостей пато-морфологічних порушень при оментитах [1,6,16].…”
unclassified